2004
DOI: 10.1103/physrevd.69.104011
|View full text |Cite
|
Sign up to set email alerts
|

Second-order perturbations of the Friedmann world model

Abstract: We consider the instability of the Friedmann world model to second order in perturbations. We present the perturbed set of equations up to second order in the Friedmann background world model with a general spatial curvature and cosmological constant. We consider systems with completely general imperfect fluids, minimally coupled scalar fields, an electromagnetic field, and generalized gravity theories. We also present the case of null geodesic equations, and one based on the relativistic Boltzmann equation. I… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
538
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 246 publications
(543 citation statements)
references
References 138 publications
(177 reference statements)
5
538
0
Order By: Relevance
“…In fact, the magnetic part of Weyl tensor does not vanish even to the linear order in perturbations: this quantity valid to the second order is presented in eq. (96) of [6]. Our nonlinear perturbation approach is applicable to fully relativistic regimes including the super-horizon scales and the early universe.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, the magnetic part of Weyl tensor does not vanish even to the linear order in perturbations: this quantity valid to the second order is presented in eq. (96) of [6]. Our nonlinear perturbation approach is applicable to fully relativistic regimes including the super-horizon scales and the early universe.…”
Section: Discussionmentioning
confidence: 99%
“…(5), and take the same identifications made in eq. (6). To the second order the perturbed part of eq.…”
Section: Second-order Perturbationsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have shown that the ϕ terms start to appear from the third order perturbation, thus in a flat background we have exact relativistic/Newtonian correspondences of the density and velocity perturbations to the second-order perturbation [5].…”
Section: Relativistic/newtonian Correspondencementioning
confidence: 57%
“…According to [29], infinitesimal diffeomorphisms may be approximated by so-called knight diffeomorphisms, which are of the form exp L ξ with ξ = λξ 1 + 1 2 λ 2 ξ 2 +O(λ 3 ). Analogously we may expand a configuration Γ as Γ = Γ 0 +δΓ = Γ 0 +λδΓ 1 + 1 2 λ 2 δΓ 2 +O(λ 3 ), and determine the transformation behaviour of separate orders by considering exp L ξ Γ at fixed order in λ, see for example [4,6,19,21,23]. Assuming that ξ and δΓ vanish at spatial infinity, each order ξ i and δΓ i may be uniquely decomposed as in (2.4) and (2.3).…”
Section: Jhep08(2016)032mentioning
confidence: 99%